Balanced parenting with young children : relationship focused parent training within a dialectical framework : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Wellington, New Zealand - Couch, Clare Mary (Massey University, 2009)
While traditional behavioural parent training programmes have assisted families with concerns of child behaviour problems, they have not kept abreast with recent conceptualisations of the development of problematic behaviours in the parent-child relationship. Research has indicated that understanding of this relationship needs to go beyond bidirectional explanations and that a dialectical framework better describes the complexity of this relationship, which, in turn, should be reflected in the parent training programmes offered. Therefore, this study provided a parent training programme focused on balance in the parent-child relationship, which encapsulated the complex, dialectical nature of this intimate relationship. A central implication when adopting this notion of balance was that all aspects of the programme were addressed at the parent and child level. In addition, multiple factors were addressed that included mindfulness and acceptance, dealing with emotions, understanding development, and addressing parental attributions. It was only within this overarching concept of balance and relationship factors that behavioural skills were introduced. Mechanisms of change were identified by investigating parental emotional schemas through their narratives about themselves, their child, and the programme. This research involved 23 parents with their 3-4 year-old children in a parent training programme where both the parent and child met weekly with a therapist in group parent training. The groups involved 2-hourly sessions for 5 weeks, modelled on a “coffee morning” where parents met and discussed issues and the children played alongside in the same room. A research assistant was available to play with and tend to basic needs of the children. Measures at pre-, post-treatment, and at follow-up targeted child behaviour problems, how much of a problem these were for the parents, parents’ sense of competence, parental attributions, and what was useful for parents in the programme. Results indicated that at post-treatment parents were able to address and maintain balance in their parent-child relationship and this reflected multiple dimensions of a dialectical understanding that had not been evident prior to the intervention. There was an increased mindfulness of both parent and child’s needs with a strong emphasis on an increased understanding of the child as an individual in their own right. Parents reported an increased recognition of the importance of dealing with emotions, with improved skills to be able to do this, an increased understanding of accommodating development, and an appreciation of needing to address parental attributions. In addition, there was a decrease in parent-reported intensity of child behaviour problems and how problematic these were for the parents, which were corroborated with parental verbal reports of improved child behaviour. Mechanisms of change that were identified included changes in parental attributions, parents being able to share with other parents, accessing “expert” knowledge from the programme facilitator, and gaining parental strategies. Implications for practice were discussed with suggestions for behavioural parent training programmes. In conclusion, limitations of the research and directions for future research were indicated.
Keywords: Parent-child relationship; Behavioural training; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology::380105 Social and community psychology